2007
DOI: 10.1021/bi6024758
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Topography of the Hydrophobic Anchor Sequence of Poliovirus 3A and 3AB Proteins and the Functional Effect of 3A/3AB Membrane Association upon RNA Replication

Abstract: Replication of poliovirus RNA takes place on the cytoplasmic surface of membranous vesicles that form after infection of the host cell. It is generally accepted that RNA polymerase 3D pol interacts with membranes in a complex with viral protein 3AB, which binds to membranes by means of a hydrophobic anchor sequence that is located near the C-terminus of the 3A domain. In this study, we used fluorescence and fluorescence quenching methods to define the topography of the anchor sequence in context of 3A and 3AB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
77
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 63 publications
(150 reference statements)
1
77
0
Order By: Relevance
“…The observation that expression of PV 3A by itself in HeLa cells does not inhibit GLuc secretion prompted us to determine whether one of the other membrane-binding viral nonstructural proteins (2B or 2C) of poliovirus or their precursors (2BC or 3AB) serve this function. In virus-infected cells, 2B, 2C, and 2BC are associated with membranes via their amphipathic helices, while 3A and 3AB are anchored through hydrophobic sequences (26,51,62,64). Previous studies in Vero cells infected with FMDV have shown that 2BC (or coexpression of 2B and 2C), but not 3A, inhibits ER-to-Golgi apparatus protein transport (43).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that expression of PV 3A by itself in HeLa cells does not inhibit GLuc secretion prompted us to determine whether one of the other membrane-binding viral nonstructural proteins (2B or 2C) of poliovirus or their precursors (2BC or 3AB) serve this function. In virus-infected cells, 2B, 2C, and 2BC are associated with membranes via their amphipathic helices, while 3A and 3AB are anchored through hydrophobic sequences (26,51,62,64). Previous studies in Vero cells infected with FMDV have shown that 2BC (or coexpression of 2B and 2C), but not 3A, inhibits ER-to-Golgi apparatus protein transport (43).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, it was shown that CVB3 3A inhibits transport by binding to cellular factor GBF-1 and inhibiting GBF-1 dependent COP-1 recruitment to membranes (43,44). Polypeptides 3A and 2B and their precursors, 3AB and 2BC, contain hydrophobic transmembrane regions that play a role in their effect on secretion (2,26,62). In the case of foot-and-mouth disease virus (FMDV), a picornavirus of the genus Aphthovirus, the 2BC precursor polypeptide rather than 3A or 2B is responsible for the block in the secretory pathway (43,44).…”
mentioning
confidence: 99%
“…These sequences had weakly hydrophobic cores composed of Ala with or without a few Leu (Table 1, sequences [10][11][12][13][14]. When these peptides were inserted into DOPS vesicles highly blue-shifted λmax and low Qratio values were generally observed (with the exception of KK pA 22 peptide which showed a somewhat more red shifted λmax and high Q-ratio), showing that a TM state predominated.…”
Section: The Effect Of Lipid Composition On the Stability Of The Tm Smentioning
confidence: 99%
“…The 87-amino-acid-long 3A protein has a C-terminal hydrophobic domain of 22 residues which is responsible for its direct membrane association and which has been shown to be important for PV replication by molecular genetic studies (13)(14)(15)(31)(32)(33). Membrane-bound 3AB, but not 3A, serves as a cofactor to stimulate the activity of 3D viral polymerase (3D pol ) in vitro (13).…”
mentioning
confidence: 99%